Film Review of When Two Worlds Collide, directed by Heidi Brandenburg and Mathew Orzel - Li, Fabiana (European Review of Latin American and Caribbean Studies, 2017)
When Two Worlds Collide, directed by Heidi Brandenburg and Mathew Orzel. Yachaywasi Films, Peru/USA/UK, 2016.Trailer